Development of Scientific and Methodical Competence of Teachers of Vocational Education Institutions - Kulishov, Volodymyr S. (2021)
The relevance of the studied problem is due to the growing requirements for scientific and methodical training of teachers of vocational education institutions in Ukraine in the context of improving the efficiency of the educational process of future skilled workers. The aim of the article was to investigate theoretically and to test experimentally the effectiveness of modern approaches to the development of scientific and methodical competence of teachers of vocational education institutions in Ukraine. Leading methods of research of this problem are empirical (questionnaires of teachers of vocational education institutions, observation and evaluation of the effectiveness of their scientific and methodical activities) and theoretical (comparative and substantive analysis of literature sources and regulations on the research topic, a systematic approach to the structure and modeling of the development of scientific and methodical competence of the teacher of vocational education institution on modern principles). It was developed and represented the structure and define levels of development of scientific and methodical competence of the teacher of vocational education institution, and also describe the process of development of scientific and methodical competence by improving the content and procedural components of advanced training of teachers of vocational education institutions. The materials of the article will be useful to the managers of vocational education institutions in the context of improving the scientific and methodical work of the institution, lecturers of postgraduate education institutions, whose activities are directly related to the professional development of pedagogical staff of vocational education institutions.